Why politics needs religion the place of religious arguments in the public square - Sweetman, Brendan (Downers Grove, Ill. : IVP Academic, 2006)
"The charge is often repeated that it is wrong to use religious arguments in public debate. But is it? In this timely book Brendan Sweetman counters this charge and the various sophisticated arguments that support it. As we witness the clash of religious and secular worldviews he argues that our pluralistic democratic society will be best served when the faith elements of secularism are acknowledged and the rational elements of religious arguments are allowed to inform the momentous debates taking place in the public square. In fact, Sweetman contends that "politics needs religion if it is to be truly democratic, concerned with fairness among worldviews, equality and a vigorous public discussion.""--Jacket.
Introduction: a new perspective on religion and politics -- Understanding worldviews -- Worldviews : the center and the outer edges -- Two major worldviews in contemporary America -- The formal structure of a worldview -- Worldviews and faith -- The rationality of worldviews -- Worldviews and religion -- Foundational and nonfoundational beliefs -- Lower-order and higher-order beliefs -- Promoting our worldview : belief, action and ritual -- The worldview of secularism -- Secularism today -- Secularism, politics and seculocracy -- The influence of secularism on religion -- Secularism as a worldview -- Secularism as a religion -- Religious beliefs and reason -- What does it mean to describe a belief as "religious"? -- Reason as a source of religious beliefs -- The rationality of religious belief -- Introducing reasonable religious beliefs into politics -- How should we handle reasonable disagreements? -- Keeping religion out of politics I -- Religious beliefs should be excluded because they are "religious" -- Traditional religious beliefs cannot be based on reason and evidence -- "Secular reason" does not imply secularism -- Secularism can better achieve overall agreement among worldviews -- Keeping religion out of politics II -- Most religious beliefs are higher-order beliefs, and so should be kept private -- Religion is dangerous, secularism is benign -- Religious beliefs should not be forced by law on those who do not think they are true -- Religious views should be excluded according to the U.S. constitution -- Rawls, religion and democracy -- Arguing from within our worldview -- John Rawls's political liberalism -- Problems with Rawls's theory -- Religion and democracy -- The principle of religious freedom -- Religion in politics -- Introducing lower-order, rational beliefs into public arguments -- A seculocracy for a secularist people? -- Some practical applications -- The relationship between church and state -- A fictional example : form and content -- Looking at the world upside down : on revising our terminology -- Pluralism, relativism and religious debates : American style -- American pluralism -- School prayer -- Display of traditional religious symbols in public places -- Religion and moral issues : the euthanasia debate in Oregon -- Moral relativism in American culture -- The problems with relativism -- The rhetoric of relativism -- Tolerance : traditional and contemporary meanings.
Includes bibliographical references (p. [251]-252) and index.
Description based on print version record.
Keywords: Religion and politics; Politik; Religion; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books